Evaluation of the Pharmacotherapy Complexity Index in Patients of a Renal Transplant Clinic - Galato, Dayani; Godoy Simões, Isabela; Santana da Silva Soares, Letícia (Brazilian Journal of Transplantation, 2022)
Objective: To evaluate the complexity of pharmacotherapy of kidney transplant patients in an outpatient clinic in the Brazilian Central-West region. Methods: This is a study that respects a descriptive cross-sectional design to evaluate the complexity index of pharmacological treatment through the documentary analysis of medical records. To calculate this index, the patient’s continuous use medications were considered, and the Pharmacotherapy Complexity Index (PCI) was adopted. To determine the PCI classification ranges, analysis of a larger group of patients (significant sample) was performed, and the quartiles of the PCI results were adopted. A pilot sample was used to describe the influence of drugs on PCI. Results: A total of 247 patients wereincluded in the study to define the strata of treatment complexity. The PCI in the sample ranged from 10 to 83.5, and, by quartile analysis, up to 22.5 was considered low complexity, between 22.6 and 27.0 medium complexity, between 27.1 and 36.0 high complexity, and above 36.1 very high complexity. The case study for the PCI evaluation occurred with 20 patients and demonstrated that the complexity is not defined by the immunosuppressive treatment, but by the drugs used for the underlying diseases or the health problems arising from age and immunosuppression (comorbidities). Diabetes mellitus appearsas the disease that contributes the most to complexity through the use of insulins. Conclusion: Patients with a higher number of drug doses and with conditions dependent on insulin therapy associated with immunosuppressive pharmacotherapy are the most complex and demand greater need for follow-up because of the difficulties faced in treatment.